2008
DOI: 10.4049/jimmunol.181.7.4632
|View full text |Cite
|
Sign up to set email alerts
|

Monocyte Migration and LFA-1-Mediated Attachment to Brain Microvascular Endothelia Is Regulated by SDF-1α through Lyn Kinase

Abstract: Infiltration of activated monocytes into the brain is a prerequisite for the development of various neurological disorders such as HIV-associated dementia, multiple sclerosis, and other inflammatory processes. In these pathologies, the chemokine SDF-1α (CXCL12) is over-expressed and might attract monocytes into the CNS. We demonstrate here that SDF-1α stimulates migration of monocytes through its receptor, CXCR4, and decreases monocyte adherence to surfaces coated with ICAM-1, a ligand for β2 integrins. SDF-1α… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 38 publications
0
35
0
Order By: Relevance
“…However, CXCL12 and CXCL14 were both down-regulated by >2-fold. CXCL12 stimulates the migration of T-lymphocytes, monocytes and neutrophils [47], [48]. CXCL14 (BRAK) is a chemoattractant for macrophages, immature dendritic cells and natural killer cells [49].…”
Section: Discussionmentioning
confidence: 99%
“…However, CXCL12 and CXCL14 were both down-regulated by >2-fold. CXCL12 stimulates the migration of T-lymphocytes, monocytes and neutrophils [47], [48]. CXCL14 (BRAK) is a chemoattractant for macrophages, immature dendritic cells and natural killer cells [49].…”
Section: Discussionmentioning
confidence: 99%
“…We, and others, have previously shown that Lyn kinase is involved in chemoattractant signaling (Ptasznik et al, 1995, 1996; Mócsai et al, 2000) and is required for CXCR4-mediated chemotaxis of hematopoietic cells and macrophages (Ptasznik et al, 2002; Malik et al, 2008; Tabe et al, 2012). Here we provide results indicating that Lyn is also required for CXCR4-mediated migration of stellate cells in inflamed pancreas.…”
Section: Introductionmentioning
confidence: 96%
“…26 Stromal derived factor-1 (SDF-1) is an important chemokine that is detectable in primary atherosclerotic plaques. 1 Studies have shown that SDF-1 was involved in the cellular adhesion mediated by intercellular adhesion molecule 1 (ICAM-1) and cooperated with ICAM-1 to capture progenitor cells from blood and to induce transendothelial migration of monocytes, 17 suggesting a critical role of SDF-1 in the mechanism of atherosclerosis.…”
Section: Introductionmentioning
confidence: 99%